The Urgency of Axiology for Technology in Language Learning - Putri, Idra; R, Syahrul; Mukhaiyar, Mukhaiyar; Torsten, Pafgett (al-fikrah: Jurnal Manajemen Pendidikan, 2024)
The use of technology in language learning today has brought quite a change to the development of language learning itself. This research aims to look at the role of axiology towards technology in language learning. Axiological studies of technology in language learning starting from the understanding of axiology as a branch of philosophy that studies values and evaluation. In general, axiology is one of the three main branches of philosophy, apart from epistemology and ontology. This research reveals the axiological urgency of technology in language learning. This research uses a literature study method and then looks at all the phenomena that appear in this study. Starting from the relevance of learning with technology in language learning, aesthetic values, ethical values and social values of technology in language learning, integration of technology in language learning, the relationship between axiology and learning motivation, the benefits and challenges of using technology in language learning. Technology and values should be balanced so that in the digital age, axiology serves as a guide to balance the use of technology with ethical values, ensuring that technology is used to support meaningful and responsible learning. The use of technology in language learning is very effective as long as it still applies good values in its application in learning